'Foundation of Memory'. About the experience of space and remnants of the former concentration camp at the Kl Plaszow memorial site - Owoc, Tomasz; Karski, Kamil (Protection of Cultural Heritage, 2018)
The basis for the presented article is a speech by Kamil Karski and Tomasz Owoc, which was presented during the conference „Historical Ruins - Protection, Use, Management”, between April 16-17, 2018 in Łazienki Królewskie in Warsaw. The presented article focuses on presenting the assumptions of the scenario of the planned commemoration of KL Plaszow as part of the designed Museum - Memorial Site. Text presents, the process of shaping the ruin, forgetting it, but also exploring and how the material traces of the past will be used to educate and build awareness of the historical importance of the area after the German concentration camp is presented.